2020
DOI: 10.56093/ijas.v90i1.98663
|View full text |Cite
|
Sign up to set email alerts
|

Stability of French bean (Phaseolus vulgaris) genotypes under diverse environments

Abstract: The present investigation was undertaken to ascertain stable genotypes across six environments. Twenty five genotypes of French bean were evaluated for yield and quality traits in three different locations of Punjab during 2017–18. The stability of genotypes was worked out by using Eberhart and Russel (1966) and GGE biplot models. Highly significant mean squares for environments and genotype × environment interaction were recorded for all the traits except for protein content. The linear component of genotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Stem girth showed high PCV and GCV in kharif (22.91% and 22.89%) but medium PCV and GCV in rabi (10.52% and 10.24%). Moderate PCV for head diameter by Reena et al [15] and moderate GCV for plant height, head diameter and 100 seed weight by Kumar et al [21] and Neelima et al [20]. Further, low PCV for the characters volume weight, days to 50% flowering, days to maturity and oil content was also reported by Kalukhe et al [22] and Makane et al [23].…”
Section: Variability and Heritabilitymentioning
confidence: 78%
“…Stem girth showed high PCV and GCV in kharif (22.91% and 22.89%) but medium PCV and GCV in rabi (10.52% and 10.24%). Moderate PCV for head diameter by Reena et al [15] and moderate GCV for plant height, head diameter and 100 seed weight by Kumar et al [21] and Neelima et al [20]. Further, low PCV for the characters volume weight, days to 50% flowering, days to maturity and oil content was also reported by Kalukhe et al [22] and Makane et al [23].…”
Section: Variability and Heritabilitymentioning
confidence: 78%
“…The genotypes by environment interaction was significant (P<0.05) for days to 50% flowering and significant (P<0.01) for the other traits, indicating the differential responses of genotypes to the two environments. Javed and Aslam (1995), Jan et al (2005), Kumar et al (2014) and Khan et al (2017) found significant mean squares for genotypes environment (drought, locations or salinity) their interaction for SY/P, HD, oil %, days to maturity and 100-seed weight. 53.25, and 53.67 for F 1 -hybrids, females and males; respectively with an overall mean of 52.92 (Table 4).…”
Section: Resultsmentioning
confidence: 93%
“…Rauf and Sadaqat (2007) and Salem et al (2013) indicated that sunflower genotypes differed in their tolerance to drought. The interaction of genotypes x environment was significant for SY/P (Kumar et al 2014 andKhan et al 2017). The close estimates of PCV and GCV at loamy sand and clay soils resulted in unreliable estimates of broad sense heritability of 98.85 and 96.67%; respectively.…”
Section: -4 Stalk Diametermentioning
confidence: 95%